A clinically functioning gonadotroph adenoma presenting with abdominal pain, ovarian hyperstimulation and fibromatosis. (11th December 2018) - Broughton, Chloe; Mears, Jane; Williams, Adam; Lonnen, Kathryn
Summary: Pituitary adenomas can be classified as functioning or non-functioning adenomas. Approximately 64% of clinically non-functioning pituitary adenomas are found to be gonadotroph adenomas on immunohistochemistry. There are reported cases of gonadotroph adenomas causing clinical symptoms, but this is unusual. We present the case of a 36-year-old female with abdominal pain. Multiple large ovarian cysts were identified on ultrasound requiring bilateral cystectomy. Despite this, the cysts recurred resulting in further abdominal pain, ovarian torsion and right oophorectomy and salpingectomy. On her 3rd admission with abdominal pain, she was found to have a rectus sheath mass which was resected and histologically confirmed to be fibromatosis. Endocrine investigations revealed elevated oestradiol, follicle-stimulating hormone (FSH) at the upper limit of the normal range and a suppressed luteinising hormone (LH). Prolactin was mildly elevated. A diagnosis of an FSH-secreting pituitary adenoma was considered and a pituitary MRI revealed a 1.5 cm macroadenoma. She underwent transphenoidal surgery which led to resolution of her symptoms and normalisation of her biochemistry. Subsequent pelvic ultrasound showed normal ovarian follicular development. Clinically functioning gonadotroph adenomas are rare, but should be considered in women presenting with menstrual irregularities, large or recurrent ovarian cysts, ovarian hyperstimulation syndrome and fibromatosis. Transphenoidal surgery is the first-line treatment with the aim of achieving complete remission. Learning points: Pituitary gonadotroph adenomas are usually clinically non-functioning, but in rare cases can cause clinical symptoms. A diagnosis of a functioning gonadotroph adenoma should be considered in women presenting with un-explained ovarian hyperstimulation and/or fibromatosis. In women with functioning gonadotroph adenomas, the main biochemical finding is elevated oestradiol levels. Serum FSH levels can be normal or mildly elevated. Serum LH levels are usually suppressed. Transphenoidal surgery is the first-line treatment for patients with functioning gonadotroph adenomas, with the aim of achieving complete remission.